Analysis of Money Laundering Using Banking System with Criminal Origin of Fraud (Supreme Court Decision Study No. 2770 K / Pid.Sus / 2024) - Hasbi Simanjuntak, Mhd (International Asia Of Law and Money Laundering, 2025)
Money laundering not only threatens economic stability and System Integrity financial, but also endanger the joint life of society, nation, and state based on Pancasila and the Constitution of the Republic of Indonesia in 1945 Money laundering is done to disguise the proceeds of crime. In this case, will be appointed based on criminal origin fraud. Related to case studies based on the decision of the Supreme Court Number 2770 K / Pid.Sus/2024. Fashion crime in the sector banking, in this case, using banking services. Predicate crime (origin of crime) it is a fraud defendant Tayo Tolu Omodaratan alias Adam has been proven legally and convincingly guilty of committing the act Criminal where “participated in fraud and laundering Money”